Eksplorasi Kemampuan Siswa Memecahkan Masalah Program Linier Grafik dan Soal Cerita - Ita Chairun Nissa (ARITHMETIC: Academic Journal of Math, 2021)
Linear program has a scope of material that emphasizes the method of determining the optimum value (maximum or minimum). Linear programming problems are generally presented through word problems that involve linear inequalities and straight line graphs, each of which requires different strategies and knowledge. This research was conducted to determine differences in the ability of students who solve linear program problems through word problems and graphical approach. Research subjects were 26 students at 11th grade in SMAN 7 Mataram. The research method used was mixed methods with sequential explanatory design. Quantitative data obtained through tests and qualitative data obtained through interviews. Data analysis with two-tail comparative statistical tests produced tstatistic = 3.63 > tcritical one-tail = 2.05 at α=0.05 which means that H0 is rejected. Then it can be concluded that there were significant differences in the ability of students who solved linear program problems through word problems and graphical approach. The results of this study can be used as a reference for the importance of providing students with consistent, continuous and varied problem solving experiences in their level of difficulty.